Respuesta :
We can factor the equation into:
(x-10)*(x-3)
Therefore the roots are:
X = 10
X = 3
(x-10)*(x-3)
Therefore the roots are:
X = 10
X = 3
Answer:
Option B and D are correct.
x = 3 and x = 10
Step-by-step explanation:
Given the functions:
[tex]f(x) =x^2-13x+30[/tex]
Split the middle terms:
[tex]f(x) =x^2-10x-3x+30[/tex]
Take out the common factor:
[tex]f(x) =x(x-10)-3(x-10)[/tex]
⇒[tex]f(x) =(x-10)(x-3)[/tex]
To find the zeroes of this function f(x).
Equate f(x) = 0
then;
[tex](x-10)(x-3)=0[/tex]
By zero product property: if ab=0 then a=0 or b = 0
then;
x-10 = 0 and x-3 = 0
⇒x = 10 and x = 3
Therefore, the zeros of the given function are: x = 10 and 3